THE UNSEEN STRUGGLE: A STUDY OF THE PROBLEMS AND CHALLENGES FACED BY MIGRANT WORKERS DURING THE PANDEMIC - Parveen, Sana; Savitri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The pandemic situation advocated groundbreaking challenges, especially for migrant workers employed in brick kilns, a group already facing precarious working conditions. This study examines the diverse struggles encountered by these workers during the pandemic, including economic difficulties, health risks, and emotional distress. The research highlights how the loss of income, food shortages, and the closure of local markets forced workers into debt, borrowing money at high-interest rates just to meet basic needs. Additionally, the fear of contracting COVID-19 and the subsequent isolation prevented many from seeking medical attention, further worsening their health. The emotional stress, including the inability to attend funerals or manage weddings due to travel restrictions, added significant stress. This study, conducted in a village in Hapur, Uttar Pradesh, uses a descriptive qualitative approach, with case study methodology and semi-structured interviews to explore the lived experiences of brick kiln migrants. The findings emphasize the resilience of migrant workers in the face of severe hardship while highlighting the urgent need for support systems to address both immediate and long-term needs. The study calls for comprehensive interventions to safeguard the welfare of migrant labourers, particularly during times of crisis.